Sleep in pituitary insufficient patients compared to patients with depression and healthy controls at baseline and after challenge with CRH. (October 2020) - Künzel, Heike; Kluge, Michael; Zeising, Marcel; Schopohl, Jochen; Yassouridis, Alexander; Stalla, Günther-Karl; Steiger, Axel
Abstract: Sleep disturbances are prevalent in both patients with pituitary insufficiency and with depression. The role of corticotropin releasing hormone (CRH), involved in sleep regulation, has not been fully clarified. Pituitary insufficiency is an ideal model for studying sleep-endocrine effects since no consecutive hormone releases and feedback effects occur after hormone administration. 11 male patients with a chronic insufficiency of the anterior pituitary gland (PI) and under stable hormonal substitution were studied during three consecutive nights in the sleep laboratory. The first night served for adapting to laboratory setting, during the second night placebo was administered and during the third night 4 × 50 μg CRH were injected in pulsatile fashion. Sleep parameters were additionally compared with those of 15 healthy male controls (C) and 15 male patients with depression (D). CRH administration was associated with a numerical increase of wake time (115 ± 15 to 131 ± 13 min) and a decrease of REM sleep (89 ± 8 to 80 ± 8 min), REM latency (69 ± 14 to 55 ± 9 min) and slow wave sleep (66 ± 16 to 57 ± 15 min). Yet, none of these changes reached statistical significance. PI showed a worse sleep profile as compared to both control groups, e.g. indicated by a significantly lower sleep efficiency index (PI:0.80 ± 0.03 vs. C:0.94 ± 0.01 vs. D:0.87 ± 0.03). In conclusion sleep-EEG changes after CRH in PI patients resemble those found in in part in patients with depression. Sleep in anterior pituitary insufficiency was impaired despite full hormonal substitution possibly suggesting an alteration of the receptor organisation of brain structures involved in sleep regulation.